Improving Access to and Quality of Postpartum Contraception Provision - Cooper, Michelle; Cameron, Sharon (Seminars in Reproductive Medicine, 2022)
Sexual activity and fertility can resume shortly after childbirth, but there are barriers to contraceptive access in the postpartum period. Unintended pregnancy and short interpregnancy intervals (of less than one year) can increase the risk of obstetric and neonatal complications. The antenatal period presents an opportunity to discuss contraceptive options, many of which can be safely initiated immediately after childbirth. Successful delivery of a postpartum contraception program requires an adequate number of maternity staff trained to provide the full range of methods.
Keywords: contraception; postpartum contraception; long-acting reversible contraception; health service delivery